Współczesne teksty urzędowe a zasady prostej polszczyzny (na wybranych przykładach) - Cieśla, Bartłomiej (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of the article is to analyse forty-one official documents issued by three units of public administration: a voivodeship office, district office and district employment agency. The employees of the first of these have been striving for some time for a simplification and unification of documents, using the suggestions from linguists and sometimes resorting to their own intuition. In order to reach this goal, they have set up a set of rules that they believe make the text more intelligible to their addresses. The employees of the district office and the district employment agency have never made any significant changes to the way official documents are written and have more reservations about simplifying them. The documents discussed in the article will be evaluated in the context of plain Polish language advocated for by the members of the Plain Polish Workshop at the University of Wrocław. The main thesis of the text is the indication that modernising official documents in order to simplify and standardise them is a positive and needed action that benefits not only the addressee, but also the sender of the message.